English in Automobiles Advertising (2024-2025) - Лесишин, Захар Ігорович (Київський національний університет імені Тараса Шевченка, 2025)
This research investigates the linguistic, pragmatic, and intersemiotic dimensions of English-language automobile advertising in 2024–2025, focusing on their role in shaping consumer perceptions and market success. The relevance of the study arises from the globalization of the automotive industry, where English serves as a powerful tool for crafting persuasive and emotionally engaging campaigns by brands like Tesla, BMW, Ford, Jeep, and Toyota on digital platforms. The object of the study is English-language automobile advertising in 2024–2025. The subject encompasses linguistic techniques, pragmatic strategies, and the interplay of verbal and visual elements in these campaigns. The purpose of the study is to analyze the structural, cultural, and functional aspects of English-language automotive advertising, identifying its role in forming consumer preferences, cultural adaptation, and communicative effectiveness. Research methods include theoretical analysis, content analysis, discourse analysis, comparative campaign analysis, and numerical analysis of engagement metrics on platforms such as YouTube, Instagram, and X Platform. The empirical material comprises authentic advertising texts and videos from leading automotive brands. The findings reveal that emotive language, metaphors, imperatives, and cultural references, combined with visual elements, enhance advertising persuasiveness. Digital platforms play a pivotal role in campaign localization and interactivity. Comparative analysis across market segments highlights the adaptation of linguistic strategies to mass-market, premium, and electric vehicle sectors. The study contributes to linguistics, marketing, and discourse analysis by illustrating how English shapes global advertising narratives. Its practical significance lies in offering recommendations for designing effective advertising campaigns.

Дослідження присвячене аналізу англомовної реклами автомобілів у 2024–2025 роках, з акцентом на лінгвістичні, прагматичні та інтерсеміотичні аспекти, що впливають на сприйняття споживачів і ринковий успіх. Актуальність теми зумовлена глобалізацією автомобільної індустрії, де англійська мова формує переконливі та емоційно насичені кампанії брендів, таких як Tesla, BMW, Ford, Jeep і Toyota, на цифрових платформах. Об’єктом дослідження є англомовна реклама автомобілів 2024–2025 років. Предмет дослідження охоплює мовні техніки, прагматичні стратегії та взаємодію вербальних і візуальних елементів у цих кампаніях. Мета дослідження – дослідити структурні, культурні та функціональні особливості англомовної автомобільної реклами, визначивши її роль у формуванні споживчих уподобань, культурної адаптації та комунікативної ефективності. Методи дослідження включають теоретичний аналіз, аналіз контенту, дискурсивний аналіз, зіставний аналіз кампаній та числовий аналіз метрик залучення на платформах YouTube, Instagram і X Platform. Матеріалом слугують автентичні рекламні тексти та відео провідних автомобільних брендів. Результати засвідчують, що використання емоційної лексики, метафор, імперативів і культурних референцій у поєднанні з візуальними елементами посилює переконливість реклами. Цифрові платформи відіграють ключову роль у локалізації та інтерактивності кампаній. Порівняння сегментів ринку показало адаптацію мовних стратегій до масового, преміум- і електромобільного ринків. Дослідження вносить вклад у лінгвістику, маркетинг і дискурсаналіз, демонструючи, як англійська мова формує глобальні рекламні наративи. Практичне значення полягає в рекомендаціях для створення ефективних рекламних кампаній.
Англійська мова в рекламі автомобілів (2024–2025)
Keywords: automotive advertising; intersemiotic synergy; digital platform; pragmatics; cultural adaptation; автомобільна реклама; інтерсеміотична синергія; цифрова платформа; прагматика; культурна адаптація